LINEAR PROGRAMMING: a case study for profit maximization in the production of 3D plasterboards in a micro company in the interior of São Paulo - Bento, Daniel Hatus da Silva; Caracini, Luiz Gustavo (Revista Interface Tecnológica, 2022)
The article introduces the growth and the importance of micro and small businesses to the national GDP through a survey conducted by the Getúlio Vargas Foundation. The purpose of this study is to seek the maximized profit of a micro company that produces 3D plasterboard for wall coverings, which have different production times. The methodology used for this study was based on bibliographic research and case study. A linear programming model was elaborated, and data was collected with its manager about the time and resources available for production, as well as its limitations. The company has particularities related to the amount of available raw material, which restricts its production, as well as the maximum production quantity of slabs with sockets since their storage requires exceptional care. Considering all of the facts, the importance of using linear programming to make decisions stand out, whether they are micro, small, medium, or large-sized. The ideal number of simple interlocking boards produced by a company per week can be obtained by graphical analysis.